2019
DOI: 10.3389/fonc.2019.01024
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-Correlated (RC) vs. Time-Resolved (TR) Four-Dimensional Magnetic Resonance Imaging (4DMRI) for Radiotherapy of Thoracic and Abdominal Cancer

Abstract: Recent technological and clinical advancements of both respiratory-correlated (RC) and time-resolved (TR) four-dimensional magnetic resonance imaging (4DMRI) techniques are reviewed in light of tumor/organ motion simulation, monitoring, and assessment in radiotherapy. For radiotherapy of thoracic and abdominal cancer, respiratory-induced tumor motion, and motion variation due to breathing irregularities are the major uncertainties in treatment. RC-4DMRI is developed to assess tumor motion for treatment plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 58 publications
(73 reference statements)
0
25
0
Order By: Relevance
“…More extensive details on the background and development of 4D-MRI acquisition that are beyond the scope of this manuscript can be found in several recently published review articles. 93,[132][133][134]…”
Section: B 4d-mrimentioning
confidence: 99%
“…More extensive details on the background and development of 4D-MRI acquisition that are beyond the scope of this manuscript can be found in several recently published review articles. 93,[132][133][134]…”
Section: B 4d-mrimentioning
confidence: 99%
“…Four-dimensional magnetic resonance imaging (4DMRI) has been recently studied for MR-based radiotherapy planning and MR-guided treatment delivery. [7][8][9] 4DMRI may appear in four forms: RC-based 4DMRI, dynamic 2D cine, dynamic 3D cine, and time-resolved (TR) 4DMRI. RC-4DMRI, similar to 4DCT, does not provide multi-breath motion simulation, [10][11][12][13] dynamic 2D cine MRI does not provide volumetric motion images, [14][15][16] and dynamic 3D cine cannot provide clinically acceptable spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Four‐dimensional magnetic resonance imaging (4DMRI) has been recently studied for MR‐based radiotherapy planning and MR‐guided treatment delivery 7–9 . 4DMRI may appear in four forms: RC‐based 4DMRI, dynamic 2D cine, dynamic 3D cine, and time‐resolved (TR) 4DMRI.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported a 3D-cine-guided, superresolution (SR) method to reconstruct T1w TR-4DMRI using DIR to combine two complementary image sets: adequate temporal resolution free-breathing (FB: 5 9 5 9 5 mm 3 at 2 Hz) 3D cine and high spatial-resolution breath-hold (BH: 2 9 2 9 2 mm 3 ) 3D static images. [17][18][19] Recently, this SR approach has also been implemented using cascade deep learning technique with limited training data for MR-guided adaptive radiotherapy. 20 The SR approach does not assume motion periodicity, and therefore can handle both regular and irregular motions, including breathing irregularities and nonrespiratory motions.…”
Section: Introductionmentioning
confidence: 99%
“…This novel SR approach combines three sets of MR images, rather than two in previous studies. [17][18][19] First, high-resolution (HR) T2w MRI was acquired using navigator-triggered 3-bin RC-4DMRI scan within the same imaging session of T1w HR BH and low-resolution (LR) FB 3D cine acquisitions. Second, mild binning artifacts in T2w MRI were automatically identified and corrected based on voxel intensity correlation (VIC) among adjacent slices using 2D DIR.…”
Section: Introductionmentioning
confidence: 99%